Analisis Peresepan Obat Formularium Nasional Berdasarkan Kesesuaian Restriksinya di Rumah Sakit Umum Daerah Sawah Besar Tahun 2018 - Kuncoro Adi Susanto; Maura Linda Sitanggang; Delina Hasan; Ida Chorida (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Health services provided to the public in the implementation of the National Health Insurance (NHI) includepromotional, preventive, curative and rehabilitative. In supporting the implementation of NHI, it is necessaryto make eff orts to ensure the availability, aff ordability and accessibility of medicines through the application of the National Formulary (Fornas) as a reference in health services in all health facilities. The purpose of this study was to determine the percentage of prescription drugs in accordance with the National Formulary at Sawah Besar Hospital in 2018. The research design descriptive analysis and data collection was carried out retrospectively in the form of prescribing drugs and from the Hospital Management Information System and Patient Medical Record data. This research was conducted with a sample size of around 19.690 recipes and a length of 6 months of research from July 2018 to December 2018. From the results of the study pattern of prescription writing against the suitability of the National Formulary was 71.22%. Compatibility of 75% antihyperlipidemic drugs with atorvastatin as the drug with the most non-conformity of restrictions. The conformity of antihypertension drugs 54.11% with Valsatran as one of the inconsistencies in restriction and insulin drugs, 70.03% the antihyperglycemia drug restriction inconsistencies.